2003
DOI: 10.1074/jbc.m212203200
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Silencing and DNA Methylation-sensitive Methylation-spreading Properties of the Kcnq1 Imprinting Control Region Map to the Same Regions

Abstract: The mechanisms underlying the phenomenon of genomic imprinting are poorly understood. Accumulating evidence suggests that imprinting control regions (ICR) associated with the imprinted genes play an important role in creation of imprinted expression domains by propagating parent-of-origin-specific epigenetic modifications. We have recently documented that the Kcnq1 ICR unidirectionally blocks enhancerpromoter communications in a methylation-dependent manner in Hep-3B and Jurkat cell lines. In this report we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
5
41
0
Order By: Relevance
“…It has been reported that DMR-LIT1 are an orientation-independent silencer (Du et al, 2003;ManciniDiNardo et al, 2003;Thakur et al, 2003). Thakur et al (2003) proposed that a repressive chromatin structure established at DMR-LIT1 might propagate bidirectionally along the DNA to inactivate neighboring genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that DMR-LIT1 are an orientation-independent silencer (Du et al, 2003;ManciniDiNardo et al, 2003;Thakur et al, 2003). Thakur et al (2003) proposed that a repressive chromatin structure established at DMR-LIT1 might propagate bidirectionally along the DNA to inactivate neighboring genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thakur et al (2003) proposed that a repressive chromatin structure established at DMR-LIT1 might propagate bidirectionally along the DNA to inactivate neighboring genes. Since LIT1 is an antisense noncoding transcript, the establishment and propagation of a repressive chromatin structure might be similar to that of Igf2r ICR, which contains Air, an antisense noncoding transcript of Igf2r (Sleutels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…ment of the genes on both sides of the KvDMR and their varied expression patterns make an enhancer-blocking model difficult to orchestrate. Indeed using in vitro transfection assays, the KvDMR behaved as a silencer rather than as an enhancer blocker (Mancini-DiNardo et al 2003;Thakur et al 2003). The other well-established mechanism for silencing imprinted genes is the RNAdependent silencing by an antisense transcript, as occurs at the Igf2r locus in the mouse (Sleutels et al 2002).…”
mentioning
confidence: 99%
“…Taken together, these observations demonstrate that NF-Y transcription factor is involved in the maintenance of differential epigenetic marks at the Kcnq1 ICR. We have earlier documented that the Kcnq1 ICR spreads de novo methylation into the flanking H19 coding region (8) and that this property occurs as a consequence of antisense RNA-mediated silencing. Because antisense transcription is lost in the PS4CAT1-3 constructs, we tested for the methylation spreading property of the Kcnq1 ICR in the PS4CAT1-3 construct.…”
Section: Nf-y Transcription Factor Maintains Differential Epigeneticmentioning
confidence: 99%
“…We have earlier documented that the Kcnq1 ICR behaves as a bidirectional silencer (8). More recently, by selectively deleting the region spanning the antisense promoter and attenuating the antisense transcription by poly(A) sequence, we have shown that the production of an antisense RNA, Kcnq1ot1, is critical in the bidirectional silencing property of the Kcnq1 ICR (3).…”
mentioning
confidence: 95%